Development of Story Books Containing MELESAT (Mathematics, Existence, Literacy, Engineering, Science, Art, Technology) to Improve Literacy Skills among Group B of Early Childhood Education - Miftakhul Jannah; Rachma Hasibuan; Ruqoyyah Fitri; Ajeng Putri Pratiwi; Andy Ledy Permata Putri (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
The purpose of this study was to develop a storybook containing Mathematics, Existence, Literacy, Engineering, Science, Art, Technology (MELESAT) to improve literacy skills among group B of early childhood education and to test the feasibility of designing a storybook containing MELESAT. This type of research is a Research and Development with Pretest - Posttest One Group Design, using the ADDIE model which includes five stages, namely Analysis, Design, Develop, Implementation, and Evaluate. Subjects are children aged 5-6 years, including group B early childhood education totally 20. The instrument used a validation questionnaire and literacy tests. Results of this research indicate that the validation of the material obtained 3.04 of 4, validation of book design obtained 2.55 of 4 and validation of the media obtained 2.89 of 4. The effectiveness based on giving pretest and posttest to students totaled 20 subjects. The results showed that the pre-test score of 57% was developing as expected, and 43% was starting to develop. Post-test scores showed 7.5% progressed beyond expectations, 87.5% progressed as expected, and 5% started to develop. Through the content, design, and use of MELESAT books, there is an increase of literacy skills of children aged 5-6 years including group B early childhood education.